The RCEP and Its Relevance to the EU - Michael Frenkel; Tuyet Ngo (Wirtschaftsdienst)
Abstract The Regional Comprehensive Economic Partnership (RCEP) is a multilateral free trade agreement (FTA) between the member countries of the Association of Southeast Asian Nations (ASEAN) and five Asia-Pacific countries, with which ASEAN has existing FTAs in the Asia-Pacific region. It was initiated with the aim to broaden and deepen regional trade and investment among the signatories. The agreement was finalised and signed in November 2020. It is now the largest free trade agreement in the world. The article examines the expected effects and their implications for the EU. It also outlines strategic ways in which the EU could respond to this new agreement.